Peeling method
By setting the glass transition temperature Tg1 of the adhesive layer to 12°C or less and cooling to a temperature of 5°C higher than Tg1, the problem of the adhesive material not easy to peel off in a high temperature environment is solved, and the easy to peel off of the adhesive material is achieved.
Patent Information
- Application Number
- CN202380050277.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-17
- Filing Date
- 2023-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
When the prior art attempts to peel off the adhesive material from the adhesive through external stimulation such as heat or energy rays, it faces problems such as reduced adhesiveness, insufficient heat resistance, and difficult adhesive material to peel off.
By setting the glass transition temperature Tg1 of the adhesive layer to 12°C or less, and after the adhesive material is pasted on the adhesive material, the adhesive layer is cooled to a temperature below 5°C higher than Tg1, thereby achieving ease of adhering the adhesive material Peelization.
It is realized that the adhesive material is simply peeled from the adhesive without affecting the adhesive strength of the adhesive material, which is suitable for applications in high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application claims priority based on Japanese Patent Application No. 2022-184066 filed on November 17, 2022, the entirety of which is incorporated herein by reference.
[0002] The present invention relates to a peeling method, and more particularly, to a peeling method for peeling an adhesive material adhered to an adherend via an adhesive layer from the adherend. Background Art
[0003] Conventionally, various techniques have been proposed for peeling an adhesive material such as a film or a label from an adherend by applying an external stimulus to the adherend (see, for example, Patent Documents 1 and 2).
[0004] Patent Document 1 discloses a technique in which the adhesive material is peeled off from the adherend by applying heat to the adherend to which the adhesive material is adhered via an acrylic adhesive containing heat-expandable microspheres. In addition, Patent Document 2 discloses a technique in which the adhesive material is bonded to the adherend via an adhesive layer formed by using an adhesive composition containing an acrylic copolymer, an energy-ray polymerizable urethane acrylate oligomer, and an energy-ray polymerizable compound having one acryloyl group or methacryloyl group in the molecule, and when peeling the adhesive material, the adhesive material is peeled off from the adherend by irradiating energy rays.
[0005] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2003-160765 Patent Document 2: Japanese Patent Application Laid-Open No. 9-291258 Summary of the invention Technical problem to be solved by the invention However, as in Patent Document 1, when an additive for responding to external stimuli is added to the adhesive layer, the adhesiveness is reduced due to the additive, and there is a concern that the strict requirements for durability in recent years cannot be met. In addition, when it is desired to achieve easy peeling by heat, for example, in applications that are expected to be used in high-temperature environments such as in the automotive field, it is necessary to maintain high adhesion in the use environment so that the adhesive material does not peel off from the adherend, and to peel the adhesive material from the adherend at a temperature higher than the use environment temperature. In this case, in order to peel the adhesive material from the adherend, there is a concern that a high temperature exceeding the heat resistance of the adherend may be required.
[0006] In addition, in the technology of peeling off the adhesive material pasted to the adherend by irradiation of energy rays as in Patent Document 2, it is considered that the adhesive material cannot be easily peeled off from the adherend when the adhesive material is a material that is non-transparent to the energy rays. In addition, in the case of using an adhesive material that can transmit energy rays, it is also considered that the adhesive material is gradually peeled off due to sunlight, and it is considered that the application to products that are intended to be used outdoors is limited. Therefore, as a method for maintaining the state of firmly adhering the adhesive material to the adherend under the use environment and easily peeling the adhesive material from the adherend by external stimulation, it is required to develop a new method different from the past.
[0007] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a peeling method capable of easily peeling an adhesive material firmly adhered to an adherend from the adherend.
[0008] Technical solutions for solving technical problems The present inventors have conducted intensive studies to solve the above-mentioned technical problems and have found that there is a correlation between the glass transition temperature of the entire adhesive layer and easy peeling. Specifically, the present invention provides the following solutions.
[0009] [1] A peeling method, which is a peeling method for peeling an adhesive material adhered to an adherend from the adherend, wherein the adhesive material is adhered to the adherend via an adhesive layer, the glass transition temperature Tg1 of the adhesive layer as a whole is below 12°C, and in a state where the adhesive material is adhered to the adherend via the adhesive layer, the adhesive layer is cooled to a temperature below 5°C higher than the glass transition temperature Tg1, thereby peeling the adhesive material from the adherend.
[0010] [2] The peeling method according to [1] above, wherein the adhesive layer is a pressure-sensitive adhesive layer.
[0011] [3] The peeling method according to [2] above, wherein the adhesive layer contains an acrylic adhesive polymer.
[0012] [4] The peeling method according to [3] above, wherein the acrylic pressure-sensitive adhesive polymer has a glass transition temperature of -80°C or higher and less than 10°C.
[0013] [5] The peeling method according to [3] or [4] above, wherein the acrylic pressure-sensitive adhesive polymer contains a structural unit UA derived from at least one selected from an alkyl (meth)acrylate having an alkyl group having 1 to 8 carbon atoms and an alkoxyalkyl (meth)acrylate having an alkoxy group having 1 to 4 carbon atoms.
[0014] [6] The peeling method according to [5] above, wherein the content ratio of the structural unit UA is 70% by mass or more relative to all monomer units of the acrylic pressure-sensitive adhesive polymer.
[0015] [7] The peeling method according to any one of [1] to [6] above, wherein the adhesive layer is formed by an adhesive composition containing an acrylic adhesive polymer, and the adhesive composition contains 70% by mass or more of the acrylic adhesive polymer relative to the total amount of polymers contained in the adhesive composition.
[0016] [8] The peeling method according to [7] above, wherein the adhesive composition further comprises a vinyl polymer having a glass transition temperature of 30° C. to 200° C. and a number average molecular weight of 500 to 10,000.
[0017] [9] The peeling method according to [8] above, wherein the content of the vinyl polymer is 0.5 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the acrylic pressure-sensitive adhesive polymer.
[0018]
[10] The peeling method according to any one of [1] to [9] above, wherein the storage modulus of the adhesive layer at a temperature 5° C. higher than the glass transition temperature Tg1 is 1 MPa or more and 1000 MPa or less.
[0019]
[11] The peeling method according to any one of [1] to
[10] above, wherein the cooling temperature is 0° C. or lower.
[0020]
[12] The peeling method according to any one of [1] to
[11] above, wherein the peel strength of the adhesive layer to an ABS plate under the conditions of 85° C. and a peeling speed of 300 mm / min is 3 N / 25 mm or more.
[0021]
[13] The peeling method according to any one of [1] to
[12] above, wherein the adhesive material is in a film or plate shape.
[0022]
[14] The peeling method according to any one of [1] to
[13] above, wherein the adhesive material is a decorative film.
[0023]
[15] The peeling method according to any one of [1] to
[13] above, wherein the adhesive material is a glass plate.
[0024] Effects of the Invention According to the present invention, even when the adhesive material is firmly adhered to the adherend via the adhesive layer, the adhesive material firmly adhered to the adherend can be easily peeled from the adherend by at least a simple process of cooling the adhesive layer. DETAILED DESCRIPTION
[0025] The present invention will be described in detail below. It should be noted that "(meth)acrylic acid" in the present specification refers to acrylic acid and / or methacrylic acid. "(meth)acrylate" refers to acrylate and / or methacrylate.
[0026] The present invention relates to a peeling method for peeling an adhesive material adhered to an adherend from the adherend by cooling. First, the adhesive material, the adherend and the adhesive layer in the peeling method of the present invention (hereinafter also referred to as "this method") are described.
[0027] <Paste material> The material and shape of the adhesive material are not particularly limited. When the adhesive material is film-shaped or plate-shaped, the adherend and the adhesive material are firmly bonded on the surface, and it is sometimes difficult to peel the adhesive material from the adherend. On the other hand, according to this method, even if the adhesive material is film-shaped or plate-shaped, it is preferred in that the adhesive material can be simply peeled off from the adherend by a relatively simple operation such as cooling treatment. In addition, according to this method, by locally cooling the position where the adhesive material is to be peeled off from the adherend, the adhesive material at the position where it is to be peeled off can also be locally peeled off from the adherend.
[0028] When the adhesive material is in a film form, the adhesive material is preferably a resin film. According to this method, even when the film-shaped adhesive material is firmly attached to a wide range of the surface of the adherend, the adhesive material can be easily peeled off from the adherend.
[0029] When the adhesive material is in the form of a film, a preferred form of the adhesive material is a decorative film. As an example of a decorative film, there can be mentioned a single-layer film in which a decorative layer is formed by coloring a base layer, and a laminated film in which a decorative layer and a base layer are laminated in sequence. The decorative film of this structure is preferably used as a decorative film for a laminated method to obtain a decorative molded body by attaching it to an adherend.
[0030] In the decorative film, after the adherend is decorated with the decorative film, the substrate layer is located at the outermost layer of the decorated adherend (i.e., the decorative molded body), and functions as a protective layer of the decorative molded body. The material constituting the substrate layer is preferably a flexible material, preferably a resin material. More preferably, it is a thermoplastic resin. The thermoplastic resin is not particularly limited, and examples thereof include: vinyl chloride (PVC) resin, polyester resin, acrylic resin, acrylonitrile-butadiene-styrene (ABS) resin, polycarbonate resin, polypropylene resin, and polyethylene resin. Among them, the substrate layer is preferably formed by at least one selected from PVC resin, polyester resin, and ABS resin.
[0031] The thickness of the substrate layer is preferably 25 μm to 500 μm, more preferably 50 μm to 400 μm, and further preferably 100 to 300 μm. When the thickness of the substrate layer is within the above range, when the decorative molded body is manufactured by injection molding (also called insert molding), vacuum molding, vacuum press molding, etc., the processability, shape tracking property and operability are good.
[0032] The decorative layer is an ink layer to which patterns or designs such as text, graphics and trademarks are given by printing or the like. The decorative film is given designability by the decorative layer. The patterns and patterns of the decorative layer can be formed by known printing methods such as gravure printing, offset printing, screen printing, transfer printing from a transfer sheet, sublimation transfer printing, and inkjet printing using printing ink. The thickness of the decorative layer is preferably 1 μm to 40 μm, and more preferably 1 μm to 30 μm. If the thickness of the decorative layer is within the above range, it is possible to ensure a thickness sufficient to express complex designs such as gradients. It is also possible to give a concave-convex pattern to the surface of the decorative film. The concave-convex pattern can be formed, for example, by transferring the concave-convex pattern using an embossing roller. In addition, by making the substrate layer and the adhesive layer contain pigments, dyes, highlighters, etc., it is also possible to give the substrate layer and the adhesive layer a decorative function.
[0033] It should be noted that the decorative film before being attached to the adherend may further have a peeling layer on the outermost layer on the adhesive layer side together with the adhesive layer. The peeling layer can prevent unwanted adhesion and is peeled off when the decorative film is attached to the adherend. The material constituting the peeling layer is not particularly limited, and for example, resin materials such as polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefins such as polypropylene and polyethylene, and paper materials such as cellophane, kraft paper, and clay-coated paper can be used. The thickness of the peeling layer can be about 10 to 400 μm.
[0034] In addition, the decorative film may also be a film having the following structure: before being attached to the adherend, the release layer of the release film having the release layer has a hard coating layer (protective layer) and a decorative layer, and is attached to the adherend via an adhesive layer provided on the decorative layer side. The decorative film having this structure is suitable for use as a transfer film. According to the decorative film having this structure, a decorative molded body can be obtained by a transfer method of transferring the hard coating layer to the adhesive layer to the adherend.
[0035] The hard coat layer is preferably composed of a material that can be cured and / or crosslinked by irradiation with active energy rays after being transferred to the adherend. Examples of materials constituting the hard coat layer include: polymers or oligomers having a (meth)acryloyl group, materials that are formed into a semi-cured state by irradiating an active energy ray-curable composition with an appropriate amount of active energy rays, or materials that are formed by mixing an isocyanate compound and a polyol resin in an active energy ray-curable resin composition and crosslinking appropriately. The thickness of the hard coat layer is not particularly limited, and is, for example, about 1 to 50 μm.
[0036] When the adhesive material is in the form of a plate, the material constituting the adhesive material may be resin, metal, ceramic, glass or a combination thereof. When the adhesive material is a glass plate, a preferred embodiment of the adhesive material is a glass plate for a display device. As a specific example of a glass plate for a display device, a front panel of the outermost layer provided on the visible side of a display device for the purpose of protecting a display module in a display device for various purposes such as a display for an automobile, a display for a game console, a smart phone, and a tablet terminal may be cited. The front panel is bonded to the main body constituting the display module via an adhesive layer (preferably an adhesive layer).
[0037] <Adhesion> The adherend is not particularly limited, and examples thereof include articles formed of resin, metal, ceramic, glass or a combination thereof. The adherend may be a finished product or a component. As for the use of the adherend or the adherend to which the adhesive material is attached, specifically, various household appliances such as household appliances, kitchen appliances, health appliances, seasonal appliances, etc.; interior and exterior components of residential equipment such as toilets, bathrooms, doors, walls, etc.; automotive interior and exterior accessories such as bumpers, instrument panels, doors, roofs, engine hoods, etc.; various sundries such as daily groceries; various display devices such as automotive displays, game console displays, mobile phones, smart phones, tablet terminals, personal computers, game consoles, clocks, etc.; electronic components; nursing and medical supplies; interior and exterior accessories of ships and aircraft, etc.
[0038] For example, in the case where a decorative film is attached to an adherend via an adhesive layer to obtain a decorative molded body, it can be carried out by vacuum forming, vacuum pressure forming, injection molding, etc. In the vacuum forming method, the decorative film is heated to soften and spread, and the space on the molded body side of the decorative film is decompressed, thereby molding and bonding the decorative film along the surface shape of the adherend. In the vacuum pressure forming method, after the molding process of the vacuum forming method, the space on the opposite side is further pressurized, thereby molding and bonding the decorative film along the surface shape of the adherend. As examples of vacuum pressure forming machines, the hot plate type decompression coating molding machine TFH series manufactured by Asano Research Institute, the TOM molding machine NGF series manufactured by Bushi Vacuum, and the NATS air transfer machine manufactured by NIS can be cited. In the injection molding method, a decorative film is set in the mold cavity of the injection molding machine, and injection molding is performed, thereby bonding the decorative film along the surface shape of the adherend. According to these methods, a decorative molded body in which the decorative film is difficult to peel off from the adherend under the use environment can be obtained.
[0039] <Adhesive layer> The adhesive layer may be formed of an adhesive or a binder. Here, an adhesive is a material that bonds objects together by changing from a liquid state to a solid state, and a binder is a material that has adhesive properties before and after bonding objects together. From the perspective of the high effect of easy peeling based on this method, the adhesive layer is preferably a layer formed of a binder (i.e., a binder layer), and more preferably a layer containing an acrylic adhesive polymer.
[0040] (Glass transition temperature) The adhesive layer has a glass transition temperature (Tg), and the Tg (Tg1) of the adhesive layer as a whole is 12°C or less. If the Tg of the adhesive layer as a whole is higher than 12°C, there is a tendency that the adhesiveness under low temperature conditions is poor, for example, the application of products intended to be used in cold regions is sometimes limited. From the viewpoint of obtaining an adhesive layer with high adhesiveness under low temperature conditions, the Tg of the adhesive layer as a whole is preferably 10°C or less, more preferably 5°C or less, further preferably 0°C or less, further preferably -5°C or less, further preferably -10°C or less, further preferably -15°C or less, particularly preferably -20°C or less, and more particularly preferably -30°C or less. In addition, the Tg of the adhesive layer as a whole is preferably -80°C or more, more preferably -70°C or more, and further preferably -60°C or more. It should be noted that the Tg of the adhesive layer as a whole is a value obtained by using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min and a nitrogen atmosphere as the measurement atmosphere. The details of the measurement conditions are described in the examples described later.
[0041] (Adhesive layer) When the adhesive layer is an adhesive layer, the type and composition of the adhesive composition for obtaining an adhesive layer having an overall Tg of 12°C or less are not particularly limited. From the perspective of being able to fully obtain the effect of easy peeling based on the present method and being able to form an adhesive layer that is not easily peeled under high temperature conditions and has high heat resistance, the adhesive layer is preferably formed of an adhesive composition containing an acrylic adhesive polymer (hereinafter also referred to as "the present adhesive composition"). Preferred examples of the adhesive composition constituting the adhesive layer are described below.
[0042] (Adhesive composition) ·Acrylic adhesive polymer (A) The acrylic adhesive polymer (hereinafter also referred to as "acrylic adhesive polymer (A)") contained in the present adhesive composition is a polymer containing a (meth)acrylic compound as a main monomer unit. From the perspective of being able to obtain a polymer with a low Tg and sufficient adhesiveness, the acrylic adhesive polymer (A) can preferably use a structural unit (hereinafter also referred to as "structural unit UA") derived from at least one selected from (meth)acrylic acid alkyl esters having an alkyl group with 1 to 8 carbon atoms in the alkyl ester portion and (meth)acrylic acid alkoxyalkyl esters having an alkoxy group with 1 to 4 carbon atoms. In addition, as a monomer constituting the acrylic adhesive polymer (A), one kind can be used alone or two or more kinds can be used in combination.
[0043] Specific examples of the alkyl (meth)acrylate having an alkyl group with 1 to 8 carbon atoms in the alkyl ester moiety used in the production of the acrylic adhesive polymer (A) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. Preferred monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0044] Specific examples of the alkoxyalkyl (meth)acrylate having an alkoxy group having 1 to 4 carbon atoms used in the production of the acrylic pressure-sensitive adhesive polymer (A) include methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxybutyl (meth)acrylate, butoxybutyl (meth)acrylate, and the like.
[0045] In the acrylic adhesive polymer (A), the content of the structural unit UA is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, relative to all monomer units of the acrylic adhesive polymer (A). By setting the content of the structural unit UA to 50% by mass or more, the adhesive force, initial adhesive force (tack), low-temperature adhesiveness, etc. of the adhesive layer can be sufficiently improved.
[0046] In the case where the present adhesive composition includes an acrylic adhesive polymer (A) and a vinyl polymer (B) described later, the acrylic adhesive polymer (A) may include a structural unit (hereinafter also referred to as "structural unit UA-1") derived from at least one selected from a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 4 carbon atoms in the alkyl ester portion and a (meth)acrylic acid alkoxy ester having an alkoxyalkyl group with 3 or 4 carbon atoms, from the viewpoint that the vinyl polymer (B) is easily segregated to the surface layer in the adhesive layer and the durability under high temperature conditions can be improved. In addition, by using such an (meth)acrylic acid alkyl ester and / or an alkoxy acrylate when producing the acrylic adhesive polymer (A), the elastic modulus of the acrylic adhesive polymer (A) can be improved, which is also effective in improving heat resistance. Among them, the structural unit UA-1 is preferably a structural unit derived from one selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate and methoxyethyl (meth)acrylate. The content ratio of the structural unit UA-1 in the acrylic pressure-sensitive adhesive polymer (A) is preferably 50% by mass or more, and more preferably 70% by mass or more, based on all monomer units of the acrylic pressure-sensitive adhesive polymer (A).
[0047] When producing the acrylic adhesive polymer (A), by using a monomer having a crosslinkable functional group (hereinafter also referred to as a "crosslinkable group-containing monomer"), the acrylic adhesive polymer (A) can be made to have a structure having a crosslinkable structural unit. By making the acrylic adhesive polymer (A) have a crosslinkable structural unit, the adhesiveness and durability of the adhesive layer under high temperature conditions can be further improved, which is preferred.
[0048] The crosslinkable group-containing monomer used in the production of the acrylic adhesive polymer (A) is not particularly limited. The crosslinkable group-containing monomer is preferably at least one selected from (meth)acrylic acid, a hydroxyalkyl (meth)acrylate compound, an epoxy-containing (meth)acrylate compound, and a reactive silyl-containing (meth)acrylate compound. Among them, in particular, from the perspective of having a tendency to improve the adhesive force of the acrylic adhesive polymer (A), at least one selected from (meth)acrylic acid and a hydroxyalkyl (meth)acrylate compound is preferred, more preferably at least one selected from (meth)acrylic acid and a hydroxyalkyl (meth)acrylate compound having a hydroxyalkyl group of 2 to 8 carbon atoms, and particularly preferably at least one selected from (meth)acrylic acid and a hydroxyalkyl (meth)acrylate compound having a hydroxyalkyl group of 2 to 4 carbon atoms.
[0049] When the acrylic adhesive polymer (A) has a crosslinkable structural unit, the content of the crosslinkable structural unit is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more relative to the total monomer units of the acrylic adhesive polymer (A). By making the content of the crosslinkable structural unit in the acrylic adhesive polymer (A) 0.1% by mass or more, a good crosslinked structure can be formed, and an adhesive polymer showing higher heat resistance and durability can be obtained. The upper limit of the content of the crosslinkable structural unit is not particularly limited. From the viewpoint of ensuring the flexibility of the obtained adhesive layer, it is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, and particularly preferably 10% by mass or less relative to the total monomer units of the acrylic adhesive polymer (A). It should be noted that when producing the acrylic adhesive polymer (A), only one type of crosslinkable monomer may be used, or two or more types may be used.
[0050] In addition to the above, the acrylic adhesive polymer (A) may have a structural unit derived from a monomer copolymerizable with the above monomer (hereinafter also referred to as "other monomer") within a range not impairing the adhesive performance. Examples of the other monomer include alicyclic (meth)acrylic acid ester compounds, aromatic (meth)acrylic acid ester compounds, polyalkylene glycol mono(meth)acrylate compounds, aromatic vinyl compounds, imide group-containing vinyl compounds, amino group-containing unsaturated compounds, amide group-containing unsaturated compounds, nitrile group-containing unsaturated compounds, and the like.
[0051] Specific examples thereof include alicyclic (meth)acrylic acid ester compounds such as cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.
[0052] Examples of the aromatic (meth)acrylic acid ester compound include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxymethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, and 3-phenoxypropyl (meth)acrylate.
[0053] Examples of the polyalkylene glycol mono(meth)acrylate compound include polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol-polypropylene glycol mono(meth)acrylate, polyethylene glycol-polybutylene glycol mono(meth)acrylate, methoxypolyethylene glycol mono(meth)acrylate, lauryloxypolyethylene glycol mono(meth)acrylate, stearyloxypolyethylene glycol mono(meth)acrylate, octyloxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, phenoxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, nonylphenoxypolyethylene glycol mono(meth)acrylate, nonylphenoxypolypropylene glycol mono(meth)acrylate, and nonylphenoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate.
[0054] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, β-methylstyrene, vinylxylene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, p-n-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, p-hydroxystyrene, m-hydroxystyrene, o-hydroxystyrene, p-isopropenylphenol, m-isopropenylphenol, o-isopropenylphenol, o-vinylbenzoic acid, m-vinylbenzoic acid, p-vinylbenzoic acid and divinylbenzene; and vinylnaphthalene.
[0055] Examples of the vinyl compound containing an imide group include maleimide compounds such as maleimide and N-substituted maleimide compounds; itaconimide compounds such as N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, and N-lauryl itaconimide; and N-methyl citraconimide, N-ethyl citraconimide, N-butyl citraconimide, N-octyl citraconimide, N-2-ethylhexyl citraconimide, N-cyclohexyl itaconimide, and N-lauryl itaconimide. Citraconimide compounds such as N-cyclohexylcitraconimide and N-laurylcitraconimide; (meth)acrylimide compounds such as N-(2-(meth)acryloyloxyethyl)succinimide, N-(2-(meth)acryloyloxyethyl)maleimide, N-(2-(meth)acryloyloxyethyl)phthalimide, N-(4-(meth)acryloyloxybutyl)succinimide, N-(4-(meth)acryloyloxybutyl)maleimide, and N-(4-(meth)acryloyloxybutyl)phthalimide, etc. As the vinyl compound containing an imide group, maleimide compounds can be preferably used.
[0056] Examples of the amino group-containing unsaturated compound include dimethylaminomethyl (meth)acrylate, diethylaminomethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-(di-n-propylamino)ethyl (meth)acrylate, 2-dimethylaminopropyl (meth)acrylate, 2-diethylaminopropyl (meth)acrylate, 2-(di-n-propylamino)propyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 3-diethylaminopropyl (meth)acrylate, and 3-(di-n-propylamino)propyl (meth)acrylate.
[0057] Examples of the unsaturated compound containing an amide group include (meth)acrylamide, (meth)acrylamide derivatives, and N-vinylamide monomers. Specific examples of (meth)acrylamide derivatives include tert-butyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, and (meth)acryloylmorpholine. Specific examples of N-vinylamide monomers include N-vinylacetamide, N-vinylformamide, and N-vinylisobutylamide.
[0058] Examples of the nitrile group-containing unsaturated compound include cyanomethyl (meth)acrylate, 1-cyanoethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-cyanopropyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, 4-cyanobutyl (meth)acrylate, 6-cyanohexyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 8-cyanooctyl (meth)acrylate, (meth)acrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-chloroacrylonitrile, and α-fluoroacrylonitrile.
[0059] The ratio of other monomers constituting the acrylic pressure-sensitive adhesive polymer (A) can be appropriately selected within a range that does not impair the effects of the present invention. As other monomers, one type may be used alone, or two or more types may be used in combination.
[0060] The arrangement form of the monomers in the acrylic adhesive polymer (A) is not particularly limited. Examples of the acrylic adhesive polymer (A) include random copolymers, block copolymers, alternating copolymers, and graft copolymers. From the perspective of being relatively easy to synthesize and being able to obtain a polymer with excellent adhesion, the acrylic adhesive polymer (A) is preferably a random copolymer and / or a block copolymer. Specifically, a random copolymer containing a polymer chain mainly composed of a structural unit derived from a (meth)acrylic compound, and / or a block copolymer having a polymer block (C) and a (meth)acrylic polymer block (D) containing a polymer chain mainly composed of a structural unit derived from a (meth)acrylic compound is preferred.
[0061] ·Production of acrylic adhesive polymer (A) The method for producing the acrylic adhesive polymer (A) is not particularly limited and the acrylic adhesive polymer (A) can be obtained by a known production method. For example, the acrylic adhesive polymer (A) can be obtained by polymerizing the above-mentioned monomers by a known free radical polymerization method such as solution polymerization, suspension polymerization, emulsion polymerization, or bulk polymerization.
[0062] For example, as a production method in the case of using a solution polymerization method, an organic solvent and a monomer are charged into a reactor, a polymerization initiator is added, and the polymerization is carried out by heating to 50 to 300° C. In this case, the method of charging each raw material including the monomer may be an intermittent initial all-at-once charging in which all the raw materials are charged at once, a semi-continuous charging in which at least a part of the raw materials are continuously supplied to the reactor, or a continuous polymerization method in which all the raw materials are continuously supplied and the produced resin is continuously taken out from the reactor.
[0063] Examples of organic solvents used in the solution polymerization method include cyclic ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbon compounds such as benzene, toluene and xylene, esters such as ethyl acetate and butyl acetate, ketones such as acetone, methyl ethyl ketone and cyclohexanone, and alcohols such as methyl orthoformate, methyl orthoacetate, methanol, ethanol and isopropanol. As the organic solvent, one or more of these can be used. The amount of the organic solvent used is an amount such as 1 to 50% by mass of the total amount of the monomers used in the polymerization relative to the total amount of the organic solvent and the monomers.
[0064] As the polymerization initiator, known free radical polymerization initiators such as azo compounds, organic peroxides, inorganic peroxides can be used, without particular limitation. Among them, from the perspective of easy operation in terms of safety and the side reaction during free radical polymerization, preferred azo compounds are used. In addition, as the polymerization initiator, a redox polymerization initiator comprising a known oxidizing agent and a reducing agent can be used. In addition, a known chain transfer agent can also be used together with the polymerization initiator.
[0065] Specific examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane), and dimethyl 2,2'-azobis(2-methylpropionate).
[0066] Examples of the organic peroxide include cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane.
[0067] Examples of inorganic peroxides include potassium persulfate and sodium persulfate. Examples of redox polymerization initiators include sodium sulfite, sodium thiosulfate, sodium formaldehyde sulfoxylate, ascorbic acid, ferrous sulfate, etc. as reducing agents and potassium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, etc. as oxidizing agents. When producing the acrylic adhesive polymer (A), the amount of the polymerization initiator used is, for example, 0.01 to 20 parts by mass relative to 100 parts by mass of all monomers used in the polymerization.
[0068] In the case where the acrylic adhesive polymer (A) is a block copolymer having a polymer block (C) and a (meth) acrylic polymer block (D) containing a polymer chain mainly composed of a structural unit derived from a (meth) acrylic compound, the monomer constituting the polymer block (C) is preferably one or more selected from an aromatic vinyl compound, an imide group-containing vinyl compound and a (meth) acrylic compound. As a method for producing the block copolymer, for example, various controlled polymerization methods such as living radical polymerization and living anion polymerization, and methods for coupling polymers having functional groups to each other can be cited. Among them, from the perspective of simple operation and applicability to a wide range of monomers, it is preferred to use a living radical polymerization method. When producing the acrylic adhesive polymer (A), a known method can be appropriately used as a living radical polymerization method.
[0069] The glass transition temperature (Tg) of the acrylic adhesive polymer (A) is preferably in the range of -80°C or higher and less than 10°C. If the Tg of the acrylic adhesive polymer (A) is -80°C or higher, the cohesive force of the adhesive layer can be sufficiently increased and the adhesiveness can be sufficiently ensured, which is preferred. From such a viewpoint, the Tg of the acrylic adhesive polymer (A) is more preferably -70°C or higher, further preferably -65°C or higher, and further preferably -60°C or higher.
[0070] On the other hand, if the Tg of the acrylic adhesive polymer (A) is less than 10°C, sufficient adhesion under low temperature conditions can be ensured, and the adhesive layer can have good followability to the adherend, so that a durable adhesive layer can be obtained even under high temperature conditions. The upper limit of the Tg of the acrylic adhesive polymer (A) is more preferably 5°C or less, further preferably 0°C or less, further preferably -5°C or less, further preferably -10°C or less, further preferably -20°C or less, and particularly preferably -30°C or less.
[0071] The preferred range of Tg of the acrylic adhesive polymer (A) can be determined by appropriately combining the upper limit and lower limit of the Tg. The range of Tg of the acrylic adhesive polymer (A) is more preferably in the range of -70°C to 5°C, further preferably in the range of -60°C to 0°C, further preferably in the range of -60°C to -10°C, further preferably in the range of -60°C to -20°C, further preferably in the range of -60°C to -30°C.
[0072] It should be noted that in this specification, the Tg of a polymer is a value determined by the intersection of the baseline of a heat flow curve obtained using DSC and the contact point at the inflection point. The details of the measurement conditions are described in the examples described below. The Tg of a polymer can be set to a desired value by changing the type and composition of the constituent monomers.
[0073] · Molecular weight characteristics of acrylic adhesive polymer (A) From the viewpoint of obtaining a polymer that exhibits sufficient cohesive force and good adhesiveness, the Mw of the acrylic adhesive polymer (A) is preferably 100,000 or more. By setting the Mw of the acrylic adhesive polymer (A) to be 100,000 or more, sufficient adhesiveness and solvent resistance can be ensured. The Mw of the acrylic adhesive polymer (A) is more preferably 120,000 or more, further preferably 150,000 or more, and further preferably 200,000 or more.
[0074] The upper limit of the Mw of the acrylic adhesive polymer (A) is not particularly limited, but is preferably 3,000,000 or less, more preferably 2,000,000 or less, and further preferably 1,500,000 or less, from the viewpoint of ensuring good coating properties and handling properties when forming an adhesive layer, and further ensuring ease of manufacture. The range of the Mw of the acrylic adhesive polymer (A) is preferably 100,000 or more and 3,000,000 or less, more preferably 150,000 or more and 2,000,000 or less, and further preferably 200,000 or more and 1,500,000 or less. It should be noted that in this specification, the molecular weight of the polymer is a polystyrene conversion value measured by gel permeation chromatography (GPC).
[0075] The acrylic adhesive polymer (A) preferably has a molecular weight distribution (Mw / Mn) represented by a ratio of Mw to Mn of 10.0 or less, and more preferably 9.0 or less, from the viewpoint of easily obtaining good adhesiveness and suppressing the viscosity of the adhesive composition from increasing. The lower limit of Mw / Mn of the acrylic adhesive polymer (A) is not particularly limited, and may be 1.0 or more.
[0076] From the viewpoint of sufficiently ensuring adhesion under low temperature conditions, the content of the acrylic adhesive polymer (A) in the present adhesive composition is preferably 70% by mass or more relative to the total amount of polymers contained in the present adhesive composition. From the above viewpoint, the content of the acrylic adhesive polymer (A) is more preferably 80% by mass or more, and further preferably 85% by mass or more relative to the total amount of polymers contained in the present adhesive composition.
[0077] Other ingredients The present adhesive composition may contain only the acrylic adhesive polymer (A), or may further contain various components (hereinafter also referred to as "other components") such as polymers other than the acrylic adhesive polymer (A), additives, and solvents as required. Other components that may be incorporated into the present adhesive composition are described below.
[0078] [Vinyl polymer (B)] The present adhesive composition may contain an acrylic adhesive polymer (A) and a vinyl polymer having a glass transition temperature (Tg) of 30°C or more and 200°C or less and a number average molecular weight (Mn) of 500 or more and 10,000 or less (hereinafter also referred to as "vinyl polymer (B)"). By forming an adhesive layer using an adhesive composition containing such a vinyl polymer (B) and an acrylic adhesive polymer (A), the vinyl polymer (B) can be partially segregated in the surface layer of the adhesive layer. As a result, the Tg of the surface layer of the adhesive layer can be sufficiently increased, and the adhesive strength and heat resistance under high temperature conditions can be improved.
[0079] If the Tg of the vinyl polymer (B) is 30°C or more, when the adhesive layer is formed using the adhesive composition, the Tg of the surface layer of the adhesive layer can be sufficiently increased, and the adhesive strength and heat resistance under high temperature conditions can be fully ensured. On the other hand, due to the limitation of the raw material monomer, the Tg of the vinyl polymer (B) is generally 200°C or less. The Tg of the vinyl polymer (B) is preferably 40°C or more, more preferably 50°C or more, further preferably 60°C or more, further preferably 70°C or more, and particularly preferably 75°C or more. Regarding the upper limit of Tg, it is preferably 150°C or less, more preferably 140°C or less, further preferably 130°C or less, and further preferably 120°C or less.
[0080] The preferred range of Tg of the vinyl polymer (B) can be determined by appropriately combining the upper limit and lower limit of the Tg. The range of Tg of the vinyl polymer (B) is preferably 40°C to 150°C, more preferably 40°C to 140°C, further preferably 50°C to 130°C, and further preferably 60°C to 120°C.
[0081] As the monomer constituting the vinyl polymer (B), various vinyl monomers having free radical polymerizability can be used. Examples of the vinyl monomer include hydrocarbon ester compounds of (meth) acrylic acid, aromatic vinyl compounds, unsaturated carboxylic acids, unsaturated acid anhydrides, hydroxyl-containing unsaturated compounds, amino-containing unsaturated compounds, amide-containing unsaturated compounds, alkoxy-containing unsaturated compounds, nitrile-containing unsaturated compounds, maleimide-based compounds, etc. These compounds can be used alone or in combination of two or more.
[0082] Examples of the hydrocarbon ester compound of (meth)acrylic acid include the alkyl (meth)acrylic acid ester compounds, aliphatic cyclic (meth)acrylic acid ester compounds, and aromatic (meth)acrylic acid ester compounds exemplified in the description of the acrylic adhesive polymer (A). Examples of the aromatic vinyl compound, unsaturated carboxylic acid, unsaturated acid anhydride, hydroxyl group-containing unsaturated compound, amino group-containing unsaturated compound, amide group-containing unsaturated compound, alkoxy group-containing unsaturated compound, and nitrile group-containing unsaturated compound include the same compounds as those exemplified in the description of the acrylic adhesive polymer (A).
[0083] Examples of maleimide compounds include maleimide and N-substituted maleimide compounds. Examples of N-substituted maleimide compounds include N-alkyl-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, and N-tert-butylmaleimide; N-cycloalkyl-substituted maleimides such as N-cyclopentylmaleimide and N-cyclohexylmaleimide; N-aralkyl-substituted maleimides such as N-benzylmaleimide; and N-aryl-substituted maleimides such as N-phenylmaleimide, N-(4-hydroxyphenyl)maleimide, N-(4-acetylphenyl)maleimide, and N-(4-methoxyphenyl)maleimide. In the production of the vinyl polymer (B), in addition to the above-mentioned compounds, dialkyl esters of unsaturated dicarboxylic acids, vinyl ester compounds, vinyl ether compounds, and the like may be used.
[0084] Among them, the vinyl polymer (B) is preferably a polymer having a structural unit derived from a hydrocarbon ester compound of (meth)acrylic acid from the viewpoint of having appropriate compatibility with the acrylic adhesive polymer (A). In the vinyl polymer (B), the content ratio of the structural unit derived from the hydrocarbon ester compound of (meth)acrylic acid is preferably in the range of 30% by mass or more and 100% by mass or less relative to all monomer units of the vinyl polymer (B). The content ratio of the structural unit derived from the hydrocarbon ester compound of (meth)acrylic acid is more preferably 50% by mass or more, further preferably 70% by mass or more, and further preferably 80% by mass or more relative to all monomer units of the vinyl polymer (B).
[0085] When producing the vinyl polymer (B), it is preferred to use an aliphatic cyclic ester compound of (meth)acrylic acid from the viewpoint of being able to make Tg higher and improving the adhesive strength under high temperature conditions. In the vinyl polymer (B), the content ratio of the structural unit derived from the aliphatic cyclic ester compound of (meth)acrylic acid is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, further preferably 15% by mass or more, further preferably 20% by mass or more relative to all monomer units of the vinyl polymer (B). The upper limit of the content ratio of the structural unit derived from the aliphatic cyclic ester compound of (meth)acrylic acid is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 70% by mass or less relative to all monomer units of the vinyl polymer (B). The range of the content ratio of the structural unit is preferably 1% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 80% by mass or less, further preferably 15% by mass or more and 70% by mass or less.
[0086] As the monomer constituting the vinyl polymer (B), among the above, at least one selected from the group consisting of tert-butyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate and adamantyl (meth)acrylate can be preferably used, from the viewpoint that Tg can be set high, the vinyl polymer (B) is easily segregated on the surface when forming the adhesive layer, and there is a tendency to obtain good heat resistance. Among them, isobornyl (meth)acrylate can be preferably used.
[0087] The Mn of the vinyl polymer (B) is 500 or more and 10,000 or less. By making the Mn of the vinyl polymer (B) less than 10,000, the segregation of the vinyl polymer (B) is fully generated in the adhesive layer, the adhesion and heat resistance under high temperature conditions can be fully improved, and the compatibility with the acrylic adhesive polymer (A) can be fully ensured. In addition, by making the polymer with an Mn of 500 or more in the vinyl polymer (B), the amount of polymerization initiator and chain transfer agent used in the manufacture of the polymer can be adjusted to avoid a decrease in productivity. The Mn of the vinyl polymer (B) is preferably more than 1,000, more preferably more than 1,500, and further preferably more than 2,000. The upper limit of the Mn of the vinyl polymer (B) is preferably less than 9,500, more preferably less than 9,000, further preferably less than 7,000, and further preferably less than 5,000. The range of Mn of the vinyl polymer (B) is preferably 1000 to 9500, more preferably 1000 to 9000, further preferably 1500 to 7000, and still further preferably 1500 to 5000.
[0088] In the vinyl polymer (B), the molecular weight distribution (Mw / Mn) represented by the ratio of Mw to Mn is preferably 3.0 or less from the perspective of easily obtaining good adhesive strength. Mw / Mn is more preferably 2.5 or less, and further preferably 2.0 or less. The lower limit of Mw / Mn of the vinyl polymer (B) is not particularly limited, but is 1.0 or more.
[0089] The method for producing the vinyl polymer (B) is not particularly limited, and the vinyl polymer (B) can be obtained by a known production method. The vinyl polymer (B) can also be obtained by polymerizing the above monomers by a known free radical polymerization method such as solution polymerization, suspension polymerization, emulsion polymerization, or bulk polymerization, similarly to the acrylic adhesive polymer (A). The details of the polymerization method can be applied to the description of the acrylic adhesive polymer (A).
[0090] The adhesive composition preferably contains a vinyl polymer (B) in a range of 0.5 to 60 parts by mass relative to 100 parts by mass of the acrylic adhesive polymer (A) in terms of solid content. If the content of the vinyl polymer (B) is 0.5 parts by mass or more, a sufficient amount of the vinyl polymer (B) is present in the surface layer of the adhesive layer, and the adhesive strength under high temperature conditions can be fully ensured. In addition, if the content of the vinyl polymer (B) is 60 parts by mass or less, the flexibility of the adhesive layer can be maintained at a high level, and the adhesiveness and transparency can be well maintained. From this point of view, the lower limit of the content of the vinyl polymer (B) is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and further preferably 2 parts by mass or more, relative to 100 parts by mass of the acrylic adhesive polymer (A). The upper limit of the content of the vinyl polymer (B) is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, further preferably 20 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the acrylic adhesive polymer (A).
[0091] The preferred range of the content of the vinyl polymer (B) can be determined by appropriately combining the upper limit and lower limit of the content of the vinyl polymer (B). Specifically, the range of the content of the vinyl polymer (B) is preferably 0.5 to 40 parts by mass, more preferably 0.5 to 30 parts by mass, further preferably 0.5 to 20 parts by mass, and further preferably 1 to 10 parts by mass, relative to 100 parts by mass of the acrylic adhesive polymer (A).
[0092] 〔Cross-linking agent〕 When the acrylic adhesive polymer (A) has a crosslinkable functional group, it is preferred to add a crosslinking agent that can react with the crosslinkable functional group to the adhesive composition because the adhesiveness under high temperature conditions, heat resistance and durability against temperature changes can be further improved.
[0093] Examples of the crosslinking agent (curing agent) include glycidyl compounds having two or more glycidyl groups, isocyanate compounds having two or more isocyanate groups, aziridine compounds having two or more aziridine groups, oxazoline compounds having oxazoline groups, metal chelate compounds, butylated melamine compounds, etc. Among them, isocyanate compounds are preferred from the perspective of excellent adhesive properties under high temperature conditions.
[0094] Specific examples of the cross-linking agent include polyfunctional glycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidyl xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and trimethylolpropane polyglycidyl ether.
[0095] Examples of the isocyanate compound include aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), xylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI) and tolylene diisocyanate (TODI); aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI) and lysine diisocyanate (LDI); alicyclic isocyanate compounds such as isophorone diisocyanate (IPDI), cyclohexyl diisocyanate (CHDI), hydrogenated XDI (H6XDI) and hydrogenated MDI (H12MDI); and modified isocyanate compounds such as urethane modified products, dimers, trimers, carbodiimide modified products, urea modified products, isocyanurate modified products, oxazolidinone modified products and isocyanate group-terminated prepolymers.
[0096] Examples of the aziridine compound include 1,6-bis(1-aziridinylcarbonylamino)hexane, 1,1′-(methylene-di-p-phenylene)bis-3,3-aziridinylurea, ethylenebis-(2-aziridinylpropionate), 2,4,6-triaziridinyl-1,3,5-triazine, and trimethylolpropane-tris(2-aziridinylpropionate).
[0097] When a crosslinking agent is added to the present adhesive composition, the content of the crosslinking agent in the present adhesive composition is not particularly limited. The content of the crosslinking agent is usually 0.01 to 10% by mass, preferably 0.03 to 5% by mass, and more preferably 0.05 to 2% by mass relative to the content of the acrylic adhesive polymer (A).
[0098] 〔Thickener〕 The adhesive composition may be formulated with a tackifier. Examples of the tackifier include rosin derivatives such as rosin ester, gum rosin, tall oil rosin, hydrogenated rosin ester, maleic rosin, and disproportionated rosin ester; terpene resins mainly composed of terpene phenolic resins, α-pinene, β-pinene, or limonene; coumarone-indene resins, hydrogenated aromatic copolymers, and phenolic resins. One tackifier may be used alone, or two or more tackifiers may be used in combination. The content of the tackifier is generally 0 to 30% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass, relative to the content of the acrylic adhesive polymer (A).
[0099] 〔Plasticizer〕 The adhesive composition may be mixed with a plasticizer. Examples of the plasticizer include phthalates such as di-n-butyl phthalate, di-n-octyl phthalate, bis(2-ethylhexyl) phthalate, and di-n-decyl phthalate; adipates such as bis(2-ethylhexyl) adipate and di-n-octyl adipate; sebacic acid esters; azelaic acid esters; paraffins such as chlorinated paraffin; glycols such as polypropylene glycol; epoxy-modified vegetable oils such as epoxidized soybean oil and epoxidized linseed oil; phosphates such as trioctyl phosphate and triphenyl phosphate; phosphites such as triphenyl phosphite; ester oligomers such as esters of adipic acid and 1,3-butanediol; low molecular weight polymers such as low molecular weight polybutene, low molecular weight polyisobutylene, and low molecular weight polyisoprene; and oils such as process oil and cycloparaffin oil. The content of the plasticizer is preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, relative to the content of the acrylic pressure-sensitive adhesive polymer (A).
[0100] As additives that can be formulated in the present adhesive composition, in addition to the above-mentioned crosslinking agent, tackifier and plasticizer, for example, antioxidants, ultraviolet absorbers, anti-aging agents, flame retardants, mildewproof agents, silane coupling agents, fillers, colorants, antistatic agents, etc. The content of the additives can be appropriately set according to various compounds within the range that does not impair the effects of the present disclosure.
[0101] 〔Solvent〕 The present adhesive composition may be a liquid composition obtained by dissolving or dispersing an acrylic adhesive polymer (A) and components formulated as required in a solvent. As a solvent for preparing the adhesive composition, an organic solvent capable of dissolving the acrylic adhesive polymer (A) or an aqueous medium capable of dispersing the acrylic adhesive polymer (A) may be cited. Specific examples of organic solvents include aprotic polar solvents, phenolic solvents, alcoholic solvents, ester solvents, ketone solvents, ether solvents, hydrocarbon solvents, etc. The organic solvent may be one of them or a mixed solvent of two or more. For example, a solvent-type adhesive composition may be obtained by dissolving the acrylic adhesive polymer (A) in one or more organic solvents selected from ethyl acetate, butyl acetate, methyl ethyl ketone and toluene. In addition, an emulsion-type adhesive composition may be obtained by dispersing the acrylic adhesive polymer (A) in an aqueous medium.
[0102] The adhesive composition of the present invention is not particularly limited in form as long as it contains an acrylic adhesive polymer (A). For example, in addition to the acrylic adhesive polymer (A), it may contain a monofunctional and / or polyfunctional (meth)acrylic monomer and a photopolymerization initiator, thereby forming a so-called syrup-type photocurable adhesive composition that is cured by active energy rays such as ultraviolet rays. In the case of a photocurable adhesive composition, the composition may contain a solvent such as an organic solvent, and is usually used as a solvent-free type that does not contain a solvent.
[0103] In the case of a solvent-based adhesive composition, the solid content concentration in the adhesive composition (i.e., the ratio of the mass of the components other than the solvent in the adhesive composition to the total mass of the adhesive composition) is not particularly limited, and is preferably 1 to 70% by mass. If the solid content concentration is 1% by mass or more, an adhesive layer having a sufficient thickness can be formed. In addition, if the solid content concentration is 70% by mass or less, good coating properties can be ensured, and an adhesive layer of uniform thickness can be easily formed. The solid content concentration in the adhesive composition is more preferably 5 to 50% by mass, and further preferably 10 to 45% by mass.
[0104] (Manufacturing of Adhesive Layer) The adhesive composition is applied to a separator, etc., and dried as needed to form an adhesive layer. As a separator, a resin film containing various resin materials can be used. As the resin material, polyester resins such as polyethylene terephthalate, polyethersulfone resins, acetate resins, polycarbonate resins, polyolefin resins, etc. can be cited. For example, in order to form an adhesive layer using a liquid adhesive composition, the adhesive composition is applied to the separator by a known coating method, and the solvent is removed by drying treatment such as heating. It should be noted that the heating temperature and heating time when forming the adhesive layer can be appropriately set according to the type of solvent, solid content concentration, etc. as long as the solvent can be removed. For example, in the case of an adhesive layer for a decorative film, the thickness of the adhesive layer is, for example, 2 to 200 μm. In addition, in order to make the adhesive layer a desired thickness, the film thickness of the adhesive layer can also be achieved by stacking multiple thin film adhesive layers.
[0105] (Characteristics of Adhesive Layer) From the viewpoint of suppressing the peeling of the adhesive material from the adherend in the use environment of the adherend to which the adhesive material is attached, the adhesive used for bonding the adherend to the adhesive material is required to have high adhesion. On the other hand, it is believed that when the adhesive material is attached to the adherend using an adhesive (i.e., an adhesive layer) with excellent adhesion, the adhesive material cannot be easily peeled off when it is desired to peel the adhesive material from the adherend. For example, when a film-like adhesive material such as a decorative film is attached or transferred to the adherend to give the adherend design, the decorative film is closely attached to the adherend, and it is not easy to peel off the decorative film when it is desired to replace the decorative film, and it is believed that replacement of the decorative film becomes difficult.
[0106] In addition, in display devices such as automotive displays, game console displays, mobile phones, smart phones, and tablet terminals, a front panel such as a glass plate is usually provided on the outermost layer of the visible side of the display device as a plate-shaped pasting material for the purpose of protecting the display module. For the front panel, sometimes the front panel is peeled off from the main body and re-pasted after the display device is temporarily used, or the peeled front panel is reused. In this case, it is desired to keep the front panel firmly pasted to the main body under the use environment of the display device, and to easily peel off the front panel when it is desired to peel the front panel from the main body. In addition, in the manufacturing process of the display device, if the front panel that has produced the offset of the pasting position can be peeled off by simple processing, and it is aligned and pasted again, it is considered to contribute to the improvement of productivity.
[0107] In this regard, according to this method, the adhesive material can be easily peeled off by simply cooling the adhesive layer of the adherend to which the adhesive material is attached to a predetermined temperature or less. Specific properties required of the adhesive layer for bonding the adherend to the adhesive material are as follows.
[0108] Tg of the entire adhesive layer The Tg of the entire adhesive layer (hereinafter also referred to as "first Tg") is preferably in the range of -80°C or higher and 12°C or lower. The first Tg is preferably -70°C or higher, and more preferably -60°C or higher. In addition, the first Tg is preferably 10°C or lower, more preferably 5°C or lower, further preferably 0°C or lower, further preferably -5°C or lower, further preferably -10°C or lower, further preferably -15°C or lower, particularly preferably -20°C or lower, and further particularly preferably -30°C or lower.
[0109] The range of the first Tg is more preferably a range of -70°C or more and 5°C or less, more preferably a range of -60°C or more and 0°C or less, more preferably a range of -60°C or more and -10°C or less, more preferably a range of -60°C or more and -20°C or less, and more preferably a range of -60°C or more and -30°C or less. If the first Tg is above -80°C, the cohesive force of the obtained adhesive layer can be improved, and an adhesive layer with high tensile shear bonding strength can be obtained. In addition, if the first Tg is below 12°C, an adhesive layer with high viscosity and adhesion under low temperature conditions can be obtained. It should be noted that the first Tg is a value obtained by using DSC at a heating rate of 10°C / min and a nitrogen atmosphere as the measurement atmosphere. The details of the measurement conditions are described in the embodiments described below.
[0110] ·Concentration of the vinyl polymer (B) in the surface layer of the adhesive layer When the adhesive layer is formed using an adhesive composition containing a vinyl polymer (B), the composition fraction (mass fraction W) of the vinyl polymer (B) in the surface layer of the adhesive layer is B ) can be obtained by analyzing the composition of the adhesive layer using X-ray photoelectron spectroscopy. B Specifically, it can be expressed as an index of the segregation state of the vinyl polymer (B) in the surface layer of the pressure-sensitive adhesive layer by the following formula (7) and formula (8).
[0111] W B = (mass of vinyl polymer (B)) / (total amount of vinyl polymer (B) and acrylic adhesive polymer (A)) … (7) W A =1-W B … (8) (In formula (7) and formula (8), W A is the mass fraction of the acrylic adhesive polymer (A) relative to the total amount of the vinyl polymer (B) and the acrylic adhesive polymer (A), W B is the mass fraction of the vinyl polymer (B) relative to the total amount of the vinyl polymer (B) and the acrylic adhesive polymer (A). Quality score W B When expressed as a percentage, the value is preferably 55% or more and 99% or less. Within this range, the vinyl polymer (B) is sufficiently segregated to the surface layer, and an adhesive layer showing high adhesion and durability at high temperature and high temperature and high humidity can be obtained. The mass fraction W when expressed as a percentage B More preferably, it is 60% or more, further preferably 65% or more, and further preferably 70% or more.B It is preferably 97% or less, and more preferably 96% or less.
[0112] When only one of the two outermost surfaces in the thickness direction of the adhesive layer is a low surface energy interface side, the adhesive layer can be made to contain the vinyl polymer (B) at a higher concentration only on the interface side. It should be noted that the segregation behavior of the vinyl polymer (B) to the surface layer of the adhesive layer when the adhesive layer is formed using the adhesive composition is presumed to be due to the fact that the vinyl polymer (B) and the acrylic adhesive polymer (A) are not completely compatible and are not completely phase-separated. From this viewpoint, the polarity of the vinyl polymer (B) is preferably lower than the polarity of the acrylic adhesive polymer (A).
[0113] ·Tg of the surface part of the adhesive layer By setting the concentration of the vinyl polymer (B) in the surface layer of the adhesive layer to be higher than that in other parts, the adhesive layer can have a higher glass transition temperature near the bonding interface. As a result, the adhesive layer can exert high peel strength and tensile shear bonding strength. This segregation behavior of the vinyl polymer (B) and the difference between the Tg of the surface layer of the adhesive layer and the Tg of the adhesive layer as a whole can be adjusted by appropriately setting the mixing ratio of the vinyl polymer (B) to the acrylic adhesive polymer (A), the monomer composition (polarity), molecular weight, Tg and Mw / Mn of the vinyl polymer (B), and the monomer composition of the acrylic adhesive polymer (A).
[0114] The glass transition temperature calculated from the composition of the surface layer of the adhesive layer formed by the adhesive composition, that is, when the adhesive layer is obtained by applying the adhesive composition on a separator and drying it, the Tg of the surface layer of the adhesive layer calculated from the composition of the surface layer of the adhesive layer obtained by X-ray photoelectron spectroscopy (hereinafter also referred to as "second Tg") is obtained by calculation based on the composition ratio of the vinyl polymer (B) and the acrylic adhesive polymer (A) obtained by X-ray photoelectron spectroscopy (XPS), and can be regarded as the glass transition temperature of the surface layer from the surface of the adhesive layer on the air interface side to a depth of about 5 nm. The details of the measurement method can be based on the operation described in the examples described later.
[0115] The second Tg is preferably 10 °C or higher. If the second Tg is 10 °C or higher, the temperature difference ΔTg (=Tg2 - Tg1) between the first Tg and the second Tg can be sufficiently increased, whereby the adhesiveness and durability at high temperatures or under high temperature and high humidity can be sufficiently ensured. The second Tg is more preferably 20 °C or higher, further preferably 30 °C or higher, still further preferably 40 °C or higher, and particularly preferably 60 °C or higher. The upper limit of the second Tg is not particularly limited, for example, it is 120 °C or lower. It should be noted that the second Tg can be appropriately adjusted according to the Tg of the vinyl polymer (B), the mixing ratio, the Tg of the acrylic adhesive polymer (A), etc.
[0116] From the aspect of high improvement effect of adhesiveness and durability under high temperature conditions, the second Tg is preferably 30 °C or higher than the first Tg, more preferably 50 °C or higher, further preferably 60 °C or higher, still further preferably 70 °C or higher, and particularly preferably 80 °C or higher. In addition, considering the values that the first Tg and the second Tg can take, the temperature difference between the second Tg and the first Tg is preferably 230 °C or lower, and generally 200 °C or lower.
[0117] · Storage modulus The storage modulus (G’) of the adhesive layer formed using this adhesive composition at a temperature 5 °C higher than the Tg (Tg1, the first Tg) of the entire adhesive layer is preferably 1 MPa or higher. The storage modulus is more preferably 3 MPa or higher, further preferably 5 MPa or higher, still further preferably 7 MPa or higher. The upper limit of the storage modulus is not particularly limited, for example, it is 1000 MPa or lower, and can be 500 MPa or lower.
[0118] It should be noted that in this specification, the storage modulus at a temperature 5 °C higher than the Tg of the entire adhesive layer is a value obtained by measuring the shear viscoelasticity (original Japanese: ずり粘弾性) of an adhesive layer with a thickness of 0.8 mm under the conditions of a heating rate of 2 °C / minute, a strain of 0.1%, and a measurement frequency of 1 Hz. The details of the measurement method of the storage modulus can adopt the method described in the following examples. The storage modulus can be arbitrarily adjusted by adjusting the composition of the acrylic adhesive polymer (A) and the degree of crosslinking, the glass transition temperature and the addition amount of additives such as vinyl copolymers and tackifiers. For example, as the constituent monomers of the acrylic adhesive polymer (A), one or more of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 4 carbon atoms and (meth)acrylic acid alkoxyalkyl esters having an alkoxy group with 1 to 4 carbon atoms can be used, and the storage modulus can be adjusted by adjusting the types and amounts of these monomers.
[0119] · Gel fraction In the case where the present adhesive composition contains a crosslinking agent, the gel fraction of the adhesive layer containing the present adhesive composition is preferably 50% or more. By making the gel fraction 50% or more, the heat resistance and durability to temperature changes of the adhesive layer can be fully improved. The gel fraction of the adhesive layer is more preferably 55% or more, further preferably 60% or more, and particularly preferably 65% or more. Regarding the upper limit of the gel fraction, it is preferably 95% or less, more preferably 90% or less, and further preferably 85% or less. It should be noted that in this specification, the gel fraction of the adhesive layer is the ratio of the mass W2 of the residual part of the adhesive layer remaining after solvent immersion to the initial mass W1 of the adhesive layer. The details are in accordance with the determination method of the embodiment described later.
[0120] Peel strength For an adhesive layer having an adhesive layer having a thickness of 50 μm and containing the present adhesive composition on a 100 μm thick polyethylene terephthalate (PET) film substrate, the peel strength to an acrylonitrile-butadiene-styrene (ABS) plate at 23°C and a peeling speed of 300 mm / min is preferably 15 N / 25 mm or more from the viewpoint of suppressing the adhesive material from floating and peeling off from the adherend at room temperature. The peel strength at 23°C is more preferably 20 N / 25 mm or more, and even more preferably 25 N / 25 mm or more.
[0121] In addition, the peel strength of the adhesive layer to the ABS plate at 85°C and a peeling speed of 300 mm / min is preferably 3N / 25mm or more from the viewpoint of being able to suppress the adhesive material from floating and peeling from the adherend under high temperature conditions and to produce an adhesive layer with high heat resistance. The peel strength at 85°C is more preferably 5N / 25mm or more, and further preferably 10N / 25mm or more.
[0122] For an adhesive layer having an adhesive layer having a thickness of 50 μm and comprising the present adhesive composition on a 100 μm thick PET film substrate, the peel strength to a coated steel plate at 23° C. and a peeling speed of 300 mm / min is preferably 10 N / 25 mm or more from the viewpoint of suppressing the adhesive material from floating and peeling off from the adherend at room temperature. The peel strength at 23° C. is more preferably 15 N / 25 mm or more, and further preferably 20 N / 25 mm or more.
[0123] In addition, the peel strength of the adhesive layer against the coated steel plate at 85°C and a peeling speed of 300 mm / min is preferably 3N / 25mm or more from the viewpoint of being able to suppress the adhesive material from floating and peeling from the adherend under high temperature conditions and to produce an adhesive layer with high heat resistance. The peel strength at 85°C is more preferably 5N / 25mm or more, and further preferably 10N / 25mm or more.
[0124] In addition, in this specification, peel strength is a value measured according to JIS Z-0237. The details of the measurement method are in accordance with the measurement method of the examples described later.
[0125] Haze value The adhesive layer preferably has high transparency. Specifically, regarding the haze value as an indicator of transparency, the adhesive layer is attached to a glass substrate and the measured value based on a haze meter after standing for 1 day at 23°C and 50%RH is preferably 2.0% or less, more preferably 1.5% or less, and further preferably 1.2% or less. It should be noted that the details of the method for measuring the haze value follow the method of the embodiment described later.
[0126] <Peeling method> Next, a method for peeling the adhesive material from the adherend by the present method is described. The present method includes a step of peeling the adhesive material from the adherend by cooling the adhesive layer to a temperature 5°C or lower higher than the Tg (Tg1) of the entire adhesive layer while the adhesive material is adhered to the adherend via the adhesive layer (hereinafter also referred to as a "peeling step"). It should be noted that, in the case where the adhesive layer is an adhesive layer, the "Tg of the entire adhesive layer" is equivalent to the above-mentioned "first Tg".
[0127] In the peeling process, the cooling method is not particularly limited as long as the adhesive layer between the adherend and the adhesive material can be cooled to a temperature below the target temperature in the area where the adhesive material is to be peeled off. The cooling of the adhesive layer can be carried out by, for example, appropriately using one or more of a cooling liquid (e.g., water, an organic solvent), dry ice, liquid nitrogen, a refrigerant, a freezer, a refrigerator, a cold storage, a cold storage, a cold storage room, a refrigerator, a spot cooler, etc. When cooling the adhesive layer, the part of the adherend where the adhesive material is to be peeled off can be locally cooled, or the adherend where the adhesive material is to be peeled off can be cooled as a whole. Specifically, the following methods can be cited: placing the adherend with the adhesive material in a temperature-adjustable cooling device such as a refrigerator or freezer; immersing part or all of the adherend with the adhesive material in a cooling liquid; using a spot refrigerator or the like to locally cool the part of the adherend with the adhesive material from which the adhesive material is to be peeled off; bringing the part of the adherend with the adhesive material from which the adhesive material is to be peeled off into contact with a solid coolant such as dry ice or a cooled metal sheet (for example, drawing the surface of the part from which the adhesive material is to be peeled off with dry ice or the like) for indirect cooling, etc. When peeling off the adhesive material from the adherend after the cooling treatment, for example, it can be done by peeling off the adhesive material floating from the adherend by hand, etc.
[0128] The cooling temperature of the adhesive layer for peeling the adhesive material from the adherend (hereinafter also referred to as "cooling peeling temperature Tc") is a temperature 5°C higher than the Tg of the adhesive layer as a whole. That is, the relationship of Tc≤(Tg+5) is satisfied. From the viewpoint of easily peeling the adhesive material from the adherend and minimizing the peeling residue of the adhesive layer, the cooling peeling temperature Tc is preferably a temperature 2°C higher than the Tg of the adhesive layer as a whole, more preferably below the Tg of the adhesive layer as a whole, further preferably below the temperature 1°C lower than the Tg of the adhesive layer as a whole, and further preferably below the temperature 2°C lower than the Tg of the adhesive layer as a whole. In addition, the cooling time of the adhesive layer for peeling the adhesive material is not particularly limited as long as the adhesive material can be peeled from the adherend. In order to shorten the time required for the peeling process and minimize the peeling residue of the adhesive layer, the cooling time is, for example, 5 seconds to 60 minutes, preferably 10 seconds to 30 minutes, and more preferably 30 seconds to 5 minutes.
[0129] In addition, from the viewpoint of showing adhesion to the adherend at room temperature and being able to easily peel the adhesive material from the adherend by cooling treatment, the cooling peeling temperature Tc is preferably 5°C or less, more preferably 0°C or less, further preferably -5°C or less, further preferably -10°C or less, further preferably -15°C or less, and further preferably -20°C or less. In particular, when the adhesive material can be peeled from the adherend by cooling the adherend to which the adhesive material is attached to -20°C or less, even for products that are intended to be used outdoors in cold regions or extremely cold regions, strong adhesive performance can be ensured under the use environment, and when the adhesive material is to be peeled off, the adhesive material can be easily peeled off by the peeling method of the present invention.
[0130] Here, in the automotive interior and exterior parts, in order to improve the design, VOC (Volatile Organic Compounds) response, etc., a decorative film is attached or transferred to the parts. When the decorative film is used to give the parts design, the decorative film can be attached tightly to the parts while following the height difference and concave-convex of the parts by stretching the decorative film while attaching it. On the other hand, in the technology of stretching the decorative film while attaching it to the parts, it is believed that the decorative film is easily offset, peeled off, and floated from the adherend under high temperature conditions, causing poor appearance. In particular, in the automotive field, products attached with decorative films are sometimes required to have heat resistance in an environment exceeding 100°C. Taking these aspects into consideration, it is considered to attach the decorative film to the adherend using an adhesive layer with sufficiently high adhesion under high temperature conditions, but in this case, when the decorative film is to be peeled off for the purpose of replacing the decorative film, etc., it is easy to be difficult to peel the decorative film off from the adherend. In contrast, according to this method, it is suitable for peeling off the decorative film attached to the automotive parts. That is, the decorative film is kept firmly bonded to the adherend while being attached to the adherend, and when the decorative film is to be peeled off from the adherend, the decorative film can be easily peeled off from the adherend by cooling.
[0131] Example Hereinafter, the present invention will be specifically described by way of examples. However, the present invention is not limited to these examples. It should be noted that, below, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "% by mass", respectively. The analysis method of the polymer used in each example is as follows.
[0132] <Molecular weight determination> Using a gel permeation chromatography apparatus (model name "HLC-8320", manufactured by Tosoh Corporation), the number average molecular weight (Mn) and weight average molecular weight (Mw) based on polystyrene conversion were obtained under the following conditions. In addition, the molecular weight distribution (Mw / Mn) was calculated from the obtained values.
[0133] ○Measurement conditions Column: TSKgel SuperMultiporeHZ-M × 4 columns manufactured by Tosoh Corporation Column temperature: 40°C Eluent: Tetrahydrofuran Detector: RI Flow rate: 600 μL / min <Measurement of glass transition temperature (Tg)> The glass transition temperature (Tg) of the polymer is determined by the intersection of the baseline and the tangent line at the inflection point of the heat flow curve obtained using a differential scanning calorimeter (DSC). The heat flow curve is obtained under the following conditions: about 10 mg of the sample is cooled to -50°C, held for 5 minutes, and then heated to 300°C at 10°C / min, then cooled to -50°C, held for 5 minutes, and then heated to 350°C at 10°C / min.
[0134] Measurement equipment: DSC6220 manufactured by SII NanoTechnology Measurement atmosphere: Nitrogen atmosphere <Calculation of Monomer Composition Ratio of Polymer> The monomer composition ratio of the obtained polymer was calculated from the input amount and the monomer consumption measured by gas chromatography (GC).
[0135] 1. Synthesis of acrylic adhesive polymer (A) [Synthesis Example 1] (Synthesis of Polymer A-1) 2-Methoxyethyl acrylate (hereinafter referred to as "MEA") (21 parts by mass), butyl acrylate (hereinafter referred to as "BA") (74 parts by mass), 2-hydroxyethyl acrylate (hereinafter referred to as "HEA") (5 parts by mass), and ethyl acetate (186 parts) were placed in a four-necked flask, and the mixture was fully degassed by bubbling nitrogen, and the internal temperature of the mixed solution was raised to 75°C. 2,2'-azobis(2,4-dimethylbutyronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65") (0.0486 parts by mass) was added as an initiator, and polymerization was carried out for 5 hours. Ethyl acetate was added so that the solid content concentration became 30%, and an ethyl acetate solution of polymer A-1 was obtained. The obtained polymer contained 21% by mass of MEA, 74% by mass of BA, and 5% by mass of HEA, and had Mn=120,000, Mw=483,000, and Mw / Mn=4.0. Tg was -41°C. The composition (charging ratio) and analysis results of the polymer A-1 are shown in Table 1. The monomer composition ratio of the polymer A-1 is equivalent to the charging ratio of the monomers.
[0136] [Synthesis Examples 2 to 11] (Synthesis of Polymers A-2 to A-11) The same operation as in Synthesis Example 1 was performed except that the type and amount of the raw materials charged into the flask and the reaction conditions were changed as described in Table 1 to obtain polymers A-2 to A-11. The analysis results of the obtained polymers are shown in Table 1. For polymers A-2 to A-11, the monomer composition ratio of each polymer is equivalent to the monomer charging ratio.
[0137] [Table 1] [Synthesis Example 12] (Synthesis of Polymer A-12) In a four-necked flask equipped with a stirrer and a thermometer, dibenzyl trithiocarbonate (1.59 parts by mass) as a RAFT agent, 2,2'-azobis(2-methylbutyronitrile) (hereinafter also referred to as "ABN-E") (0.255 parts by mass) as a polymerization initiator, styrene (hereinafter also referred to as "St") (37.5 parts by mass) and N-phenylmaleimide (hereinafter also referred to as "PhMI") (62.5 parts by mass) as monomers, and acetonitrile (233.0 parts by mass) as a solvent were added, and the mixture was fully degassed by nitrogen bubbling, and polymerization was initiated in a thermostatic bath at 70°C. After 3 hours, the reaction was stopped by cooling to room temperature. The polymerization solution after the reaction was stopped was reprecipitated and purified from methanol, and vacuum dried to obtain a polymer block (C). The obtained polymer block (C) had Mn=10900, Mw=12700, and Mw / Mn=1.2. The glass transition temperature Tg of the polymer block (C) was 206°C.
[0138] Next, the obtained polymer block (C) (7.0 parts by mass), ABN-E (0.0267 parts by mass) as a polymerization initiator, BA (17.0 parts by mass), MEA (78.0 parts by mass) and HEA (5.0 parts by mass) as monomers, and acetonitrile (35.7 parts by mass) as a solvent were added to a 1L flask equipped with a stirrer and a thermometer, and the mixture was fully degassed by nitrogen bubbling, and polymerization was initiated in a thermostatic bath at 70°C. After 6 hours, the mixture was cooled to room temperature, and ethyl acetate was added to adjust the solid content concentration to 30% by mass, thereby obtaining an adhesive solution of a (CDC)-type triblock copolymer A-12 having a polymer block (C) and a (meth) acrylic polymer block (D). The obtained polymer A-12 had Mn=160000, Mw=283000, Mw / Mn=1.8, and Tg of -35°C. The monomer composition and analysis results of polymer A-12 are shown in Table 2.
[0139] [Table 2] The abbreviations of the monomers in Tables 1 and 2 are as follows.
[0140] MEA: 2-Methoxyethyl acrylate MA: Methyl acrylate BA: Butyl acrylate HA: 2-Ethylhexyl Acrylate HEA: 2-Hydroxyethyl Acrylate AA: Acrylic acid St:Styrene PhMI: N-phenylmaleimide 2. Synthesis of Vinyl Polymer (B) [Synthesis Example 13] (Synthesis of Polymer B-1) A mixed solution containing butyl acetate (200 parts by mass) and dimethyl-2,2'-azobis(2-methylpropionate) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-601", hereinafter also referred to as "V-601") (0.9 parts by mass) was placed in a 4-necked flask with an internal volume of 1 liter. The mixed solution was fully degassed by bubbling with nitrogen, and the internal temperature of the mixed solution was raised to 90°C. Separately, a mixed solution containing methyl methacrylate (hereinafter also referred to as "MMA") (165 parts by mass), isobornyl methacrylate (hereinafter also referred to as "IBXMA") (44 parts by mass), V-601 (17 parts by mass), and butyl acetate (90 parts by mass) was dripped into the flask from a dropping funnel over 5 hours to perform polymerization. After the dripping was completed, the polymerization solution was dripped into a mixed solution containing methanol (4800 parts by mass) and distilled water (1200 parts by mass), thereby separating the vinyl polymer in the polymerization solution to obtain polymer B-1. The composition and analysis results of polymer B-1 are shown in Table 3. The composition ratio of the monomers constituting the obtained polymer B-1 was calculated based on the feed amount and the monomer consumption measured by GC, and the result showed that the monomers contained 80% by mass of MMA and 20% by mass of IBXMA. In addition, the molecular weight characteristics of polymer B-1 were Mw=6700, Mn=4370, and Mw / Mn=1.53. Tg was 108°C. The monomer composition and analysis results of polymer B-1 are shown in Table 3.
[0141] [Synthesis Example 14] (Synthesis of polymer B-2) A mixed solution containing butyl acetate (200 parts by mass) and V-601 (6.2 parts by mass) was placed in a four-necked flask with an internal volume of 1 liter, and the mixed solution was fully degassed by bubbling nitrogen, and the internal temperature of the mixed solution was raised to 90°C. In addition, a mixed solution containing MMA (100 parts by mass), IBXMA (109 parts by mass), V-601 (20 parts by mass) and butyl acetate (90 parts by mass) was dripped into the flask from a dropping funnel over 5 hours to perform polymerization. After the dripping was completed, the polymerization solution was dripped into a mixed solution containing methanol (4800 parts by mass) and distilled water (1200 parts by mass), thereby separating the vinyl polymer in the polymerization solution to obtain polymer B-2. The monomer composition and analysis results of polymer B-2 are shown in Table 3.
[0142] [Synthesis Example 15] (Synthesis of Polymer B-3) A mixed solution containing butyl acetate (223 parts by mass) and V-601 (1.3 parts by mass) was placed in a four-necked flask with an internal volume of 1 liter, and the mixed solution was fully degassed by bubbling nitrogen, and the internal temperature of the mixed solution was raised to 90°C. In addition, a mixed solution containing MMA (60 parts by mass), IBXMA (166 parts by mass), V-601 (25 parts by mass) and butyl acetate (90 parts by mass) was dripped into the flask from a dropping funnel over 5 hours to perform polymerization. After the dripping was completed, the polymerization solution was dripped into hexane (6000 parts by mass), thereby separating the vinyl polymer in the polymerization solution to obtain polymer B-3. The monomer composition and analysis results of polymer B-3 are shown in Table 3.
[0143] [Table 3] The abbreviations of the monomers in Table 3 are as follows.
[0144] MMA: Methyl Methacrylate IBXMA: Isobornyl methacrylate 3. Production of adhesive composition and adhesive film [Experimental Example 1] A polymer B-3 solution having a solid content concentration of 30% by mass prepared by dissolving polymer B-3 (4 parts by mass) in ethyl acetate was mixed with the polymer A-1 solution to prepare a polymer solution having a solid content of 30% by mass containing polymer A-1 (100 parts by mass) and polymer B-3 (4 parts by mass). A modified trimethylolpropane of xylylene diisocyanate (Takenate D-110N manufactured by Mitsui Chemicals, Inc., 0.53 parts by mass, solid content concentration of 75% by mass) was mixed therein as a crosslinking agent to obtain an adhesive composition.
[0145] The obtained adhesive composition was applied to a separator made of polyethylene terephthalate (hereinafter referred to as "PET") having a thickness of 50 μm so that the thickness after drying was 50 μm. The adhesive composition was dried at 80°C for 4 minutes to remove the ethyl acetate. A separator made of PET having a thickness of 38 μm and having a different peeling force from the above separator was attached and left to stand at 40°C for 5 days for aging (aging), thereby obtaining an adhesive film with a double-sided separator.
[0146] [Experimental Examples 2 to 15] Based on the compositions shown in Tables 4 and 5, an adhesive composition was prepared in the same manner as in Experimental Example 1. Using the obtained adhesive composition, an adhesive film with a double-sided tape separator was obtained in the same manner as in Experimental Example 1. In addition, the numerical values of the compositions of the adhesive compositions in Tables 4 and 5 indicate the amount (parts by mass) of the solid content for the vinyl polymer (B), the acrylic adhesive polymer (A) and the tackifier, and indicate the amount (parts by mass) of the solvent included for the crosslinking agent.
[0147] 4. Evaluation The obtained double-sided tape separator adhesive film (hereinafter referred to as “adhesive film sample”) was subjected to various measurements and evaluations by the following methods. The obtained results are shown in Tables 4 and 5.
[0148] <Gel Fraction> 0.2 g of adhesive was collected from the adhesive film sample and the initial mass of the adhesive was weighed. The adhesive was immersed in 50 g of ethyl acetate and allowed to stand at room temperature for 16 hours. Then, it was filtered with a 200-mesh metal mesh, and the remaining part on the mesh was dried at 80°C for 3 hours and weighed. The gel fraction was calculated based on the initial mass and the mass of the remaining part.
[0149] <Haze value> The release film was peeled off from the adhesive film sample (adhesive layer thickness: 50 μm), transferred to a glass plate (1 mm thick), and the other release film was peeled off. After standing for 1 day under 23°C and 50% RH conditions, the haze value was measured using a haze meter "Haze Meter NDH2000" (model name) manufactured by Nippon Denshoku Co., Ltd.
[0150] <Tg of the entire adhesive layer> The Tg of the entire pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition was measured by DSC in accordance with JIS K 7121 under the following conditions.
[0151] Measurement equipment: TA Instrument (Q-100) Heating temperature: 10℃ / min Measurement atmosphere: Nitrogen atmosphere <Surface Concentration of Vinyl Polymer (B) in Adhesive Layer and Tg of Surface Layer> The mass fractions (w / w) of the acrylic adhesive polymer (A) and the vinyl polymer (B) relative to the total amount of the acrylic adhesive polymer (A) and the vinyl polymer (B) in the surface layer of the adhesive layer were calculated from the peak area ratio of O1s to C1s obtained by X-ray photoelectron spectroscopy (XPS) of the adhesive film sample. A and w B ), the Tg of the surface layer was calculated based on the FOX formula.
[0152] In addition, the XPS measurement was performed under the following conditions.
[0153] Device: PHI5000 VersaProbe manufactured by ULVAC-PHI X-ray: Al-Kα (1486.6 eV) X-ray incident angle to the sample: 0° (angle relative to the normal line of the sample measurement surface) Photoelectron detection angle: 45° (angle relative to the normal line of the sample measurement surface) The specific calculation method of the above mass fraction is described below.
[0154] The ratio of the number of oxygen atoms to the number of carbon atoms calculated from the peak area ratio of O1s to C1s obtained by XPS measurement is expressed as the following mathematical formula (1), which is expressed by the ratio of the number of oxygen atoms to the number of carbon atoms present per unit mass of the surface layer of the adhesive layer formed by the adhesive composition containing the acrylic adhesive polymer (A) and the vinyl polymer (B).
[0155] [Number 1] in, (O / C) A+B : The ratio of the number of oxygen atoms to the number of carbon atoms calculated from the peak area ratio of O1s to C1s of the adhesive layer obtained by drying the adhesive composition by XPS measurement W A : The mass fraction of the acrylic adhesive polymer (A) relative to the total amount of the vinyl polymer (B) and the acrylic adhesive polymer (A) M w-A : Weighted average molecular weight of all monomer units constituting the acrylic adhesive polymer (A) M w-B : Weighted average molecular weight of all monomer units constituting the vinyl polymer (B) N O-A : The average number of oxygen atoms contained in the monomer structural formula of all the constituent monomers constituting the acrylic adhesive polymer (A) N O-B : The average number of oxygen atoms contained in the monomer structural formula of all the constituent monomers constituting the vinyl polymer (B) N C-A : The average number of carbon atoms contained in the monomer structural formula of all the constituent monomers constituting the acrylic adhesive polymer (A) N C-B : The average number of carbon atoms contained in the monomer structural formula of all the constituent monomers constituting the vinyl polymer (B) The ratio of the number of carbon atoms to the number of oxygen atoms calculated from the peak area ratio of O1s to C1s determined by XPS measurement of a film obtained by drying each monomer of the acrylic pressure-sensitive adhesive polymer (A) and the vinyl polymer (B) are represented by the following mathematical formulas (2) and (3), respectively.
[0156] [Number 2] in, (O / C) A : The ratio of the number of oxygen atoms to the number of carbon atoms calculated from the peak area ratio of O1s to C1s obtained by XPS measurement of a film obtained by drying the acrylic adhesive polymer (A) [Number 3] in, (O / C) B : The ratio of the number of oxygen atoms to the number of carbon atoms calculated from the peak area ratio of O1s to C1s obtained by XPS measurement of a film obtained by drying the vinyl polymer (B) The following formula (4) is derived from the above formulas (1) to (3), and the mass fraction (W) of the acrylic pressure-sensitive adhesive polymer (A) relative to the total amount of the acrylic pressure-sensitive adhesive polymer (A) and the vinyl polymer (B) is calculated. A ).
[0157] [Number 4] Furthermore, the W obtained above A The value of is used to calculate the mass fraction (W) of the ethylene polymer (B) using the following formula (5). B ).
[0158] W B =1-W A ···(5) in, W B : The mass fraction of the vinyl polymer (B) relative to the total amount of the acrylic adhesive polymer (A) and the vinyl polymer (B) Regarding Experimental Example 3, each element in the above-mentioned mathematical formula (4) is shown below.
[0159] (O / C) A+B : 0.327 (measured value) (O / C) A : 0.435 (measured value) (O / C) B : 0.309 (measured value) NC-B : Based on the number of carbon atoms in one molecule of MMA (5), the number of carbon atoms in one molecule of IBXMA (14) and the composition ratio, 5×89.9 (mol%) + 14×10.1 (mol%) = 5.91 N C-A : Based on the number of carbon atoms in one molecule of MEA (6), the number of carbon atoms in one molecule of BA (7), the number of carbon atoms in one molecule of HEA (5) and the composition ratio, 6×84.4 (mol%) + 7×10.1 (mol%) + 5×5.6 (mol%) = 6.05 M w-B : Based on the molecular weight of MMA (100), the molecular weight of IBXMA (222) and the composition ratio, 100×89.9 (mol%) + 222×10.1 (mol%) = 112.3 M w-A : Based on the molecular weight of MEA (130), the molecular weight of BA (128), the molecular weight of HEA (116) and the composition ratio, 130×84.4 (mol%) + 128×10.1 (mol%) + 116×5.6 (mol%) = 119.6 By substituting these values into the above mathematical formula (4), we can obtain W B =0.84, according to the above mathematical formula (5), we get W A =0.16.
[0160] Next, the Tg of the surface layer of the pressure-sensitive adhesive layer was calculated from the surface composition obtained in the measurement according to the FOX formula shown in the following mathematical formula (6), and a value of 75° C. was obtained.
[0161] 1 / 〔Tg of the surface layer〕(K)=W A / Tg A +W B / Tg B ···(6) in, Tg A : Tg of acrylic adhesive polymer (A) (-35°C) Tg B : Tg of vinyl polymer (B) (108°C) <Elastic modulus measurement> The adhesive film sample (adhesive layer thickness: 50 μm) was laminated until the adhesive layer became 0.8 mm thick to obtain an adhesive sheet for elastic modulus evaluation. The adhesive sheet for evaluation was punched into a circle with a diameter of 8 mm, and the dynamic viscoelasticity was measured at a frequency of 1 Hz and a strain of 0.1% using a shear viscoelasticity device (manufactured by Anton Paar, Physica MCR-301) while heating from -50°C to 150°C at 2°C / min. It should be noted that a parallel plate of 8 mmφ was used in the measurement. Tables 3 and 4 show the storage modulus at a temperature 5°C higher than the Tg (Tg1) of the entire adhesive layer obtained by DSC measurement.
[0162] <Peel test> (1) Preparation of peel test piece The adhesive film sample (adhesive layer thickness: 50 μm) was transferred to a PET film (100 μm) after easy adhesion treatment to obtain an adhesive sheet for peeling test. When the adherend was an ABS plate (manufactured by TP Giken Co., Ltd., 2 mm thick) or a coated steel plate (manufactured by Standard-Testpiece Co., Ltd., SPCC-SD, 70 mm × 150 mm size, cationic electrodeposition coating (gray) + urethane coating (white) + acrylic urethane coating 4:1 (transparent)), the above adhesive sheet for peeling test was attached and pressed for 20 seconds at 120°C and 0.8 MPa using a precision heating and pressing device (manufactured by Shinto Kogyo Co., Ltd.) to obtain a peeling test piece. When the adherend was a glass plate (Fabritec FL11A, 1 mm thick, manufactured by AGC), the above-mentioned pressure-sensitive adhesive sheet for the peel test was bonded and pressed for 20 minutes at 50° C. and 0.5 MPa using a tabletop pressure degassing apparatus TBR-200 (manufactured by Chiyoda Electric Industry Co., Ltd.) to obtain a peel test piece.
[0163] (2) Evaluation of adhesive sheet peeling For the peel test piece, a tensile testing machine Strograph R model (manufactured by Toyo Seiki Co., Ltd.) with a thermostatic chamber was used to measure the 180-degree peel strength of the adhesive sheet in accordance with JIS Z-0237 "Adhesive Tape and Adhesive Sheet Test Methods" at temperatures of -20°C, 23°C, and 85°C and a peel speed of 300 mm / min. The peel strength at each temperature was measured.
[0164] (3) Evaluation of peeling of decorative film Using a vacuum press molding machine (manufactured by NIS, NATS-0612B model), under the conditions of film heating temperature of 120°C and pressure of 0.2MPa, a decorative film sample made by laminating an adhesive film sample and an acrylic resin decorative film (manufactured by Wavelock Advanced Technology, 100μm thick) was laminated to an ABS plate (manufactured by TP Technology, 70mm×150mm×2mm size, natural) to obtain a peel test piece. Then, the peel test piece was placed in a temperature-adjustable freezer for 3 minutes and cooled to 0°C, -20°C, -25°C, -30°C, -35°C, -40°C, and -60°C. After each sample was taken out of the freezer, the decorative film was immediately peeled off by hand in a direction perpendicular to the 70mm side of the ABS plate, and the ease of peeling during peeling was evaluated by the following three-level standards. It should be noted that for the peel test piece after cooling, the surface temperature of the decorative film before peeling was measured using an infrared thermometer, thereby confirming that the adhesive layer was cooled to a specified temperature. In addition, for samples cooled to -20°C or lower, the peeling was performed after wearing protective gloves such as deerskin gloves.
[0165] Good (○): Can be easily peeled off with almost no force Possible (△): Can be peeled off if strongly stretched Defective (×): Cannot be peeled off In addition, the adherend was changed from an ABS plate to a coated steel plate (SPCC-SD manufactured by Standard-Testpiece, 70 mm × 150 mm, cationic electrodeposition coating (gray) + urethane coating (white) + acrylic urethane coating 4:1 (transparent)), and the same operation as above was performed to evaluate the ease of peeling. It should be noted that if it is "good (○)" or "acceptable (△)", it can be said to be practical.
[0166] (4) Evaluation of glass plate peeling The adhesive film sample (adhesive layer thickness: 50 μm) was bonded to two glass plates (Fabritec FL11A manufactured by AGC, 100 mm × 100 mm × 1 mm in size) and pressed for 20 minutes at 0.5 MPa and 50°C using a tabletop pressure degassing device TBR-200 (manufactured by Chiyoda Electric Industry Co., Ltd.) to obtain a peel test piece. Then, the peel test piece was placed in a temperature-adjustable freezer for 5 minutes and cooled to 0°C, -20°C, -25°C, -30°C, -35°C, -40°C, and -60°C. After each sample was taken out of the freezer, a metal plate was immediately inserted into the gap between the glass plates, and the glass plates were peeled off using the lever principle. The ease of peeling during peeling was evaluated using the following three-level standards.
[0167] Good (○): Can be easily peeled off with almost no force Possible (△): Can be peeled off if strongly stretched Defective (×): Cannot be peeled off Note that if the rating is “good (○)” or “acceptable (△)”, it can be said to be practical.
[0168] [Table 4] [Table 5] The abbreviations of the tackifiers and crosslinking agents in Tables 4 and 5 are as follows.
[0169] C-1: Product name "KE-311", rosin ester with a softening point of 90 to 100°C, manufactured by Arakawa Chemical Co., Ltd. Takenate D-110N: Takenate D-110N manufactured by Mitsui Chemicals, Inc., trimethylolpropane-modified xylylene diisocyanate, solid content concentration 75% by mass Coronate L: Coronate L manufactured by Tosoh Corporation, trimethylolpropane adduct of toluene diisocyanate, solid content concentration 75 mass % Regarding Experimental Examples 10 to 15, since the adhesive composition does not contain a vinyl polymer (B), the surface concentration of the vinyl polymer (B) in the adhesive layer and the Tg of the surface layer portion were not measured using XPS. Therefore, in Table 5, "-" is written in the columns of "Surface concentration of (B) using XPS", "Tg of (I) surface layer portion", and "(I)-(II) ΔTg" of Experimental Examples 10 to 15. It should be noted that Experimental Examples 10, 11, 13 to 15 do not contain a vinyl polymer (B) and a tackifier in the adhesive composition, so it can be considered that the Tg of the surface layer portion of the adhesive layer is the same as the Tg of the acrylic adhesive polymer (A).
[0170] Observing the results of Experimental Example 1, the Tg of the entire adhesive layer in the decorative film sample is -38°C. When the decorative molded body formed by bonding the decorative film sample to an ABS plate or a coated steel plate is cooled to 0°C, -20°C, -25°C or -30°C, the decorative film cannot be peeled off from the ABS plate and the coated steel plate. In contrast, by cooling the decorative molded body to -35°C, -40°C or -60°C, the decorative film can be peeled off from the ABS plate and the coated steel plate with almost no residual adhesive (Table 4). In addition, for Experimental Examples 2 to 15, by cooling the decorative molded body to a temperature below the Tg of the entire adhesive layer or a temperature close thereto, the decorative film can be kept bonded to the ABS plate and the coated steel plate before cooling, and the decorative film can be easily peeled off from the ABS plate and the coated steel plate by cooling (Tables 4 and 5).
[0171] In addition, when the adherend is a glass plate, by cooling the peel test piece to a temperature below the Tg of the entire adhesive layer or a temperature in the vicinity thereof, the two glass plates can be kept bonded by the adhesive layer before cooling, and the other glass plate can be easily peeled off from one glass plate by cooling (Table 4, Table 5).
[0172] From the above results, it is understood that according to the peeling method of the present invention, an adhesive material firmly adhered to an adherend can be easily peeled from the adherend.
[0173] The present invention is not limited to the above-mentioned embodiments, and also includes various modifications and variations within the scope of the present invention without departing from the main purpose of the present invention. Therefore, it should be understood that according to the above teachings, various combinations, forms, and other combinations and forms including only one element, more than one element, or less than one element also fall into the category and scope of the present invention.
Claims
1. A method for peeling an adhesive material adhered to an adherend from the adherend, characterized in that: The adhesive material is adhered to the adherend via the adhesive layer. The glass transition temperature Tg1 of the adhesive layer as a whole is 12°C or less, In a state where the adhesive material is attached to the adherend via the adhesive layer, the adhesive layer is cooled to a temperature 5° C. or lower higher than the glass transition temperature Tg1, thereby peeling the adhesive material from the adherend.
2. The stripping method according to claim 1, wherein: The bonding layer is an adhesive layer.
3. The stripping method according to claim 2, wherein: The adhesive layer includes an acrylic adhesive polymer.
4. The stripping method according to claim 3, wherein: The acrylic pressure-sensitive adhesive polymer has a glass transition temperature of -80°C or higher and lower than 10°C.
5. The stripping method according to claim 3, wherein: The acrylic pressure-sensitive adhesive polymer includes a structural unit UA derived from at least one selected from an alkyl (meth)acrylate having an alkyl group having 1 to 8 carbon atoms and an alkoxyalkyl (meth)acrylate having an alkoxy group having 1 to 4 carbon atoms.
6. The stripping method according to claim 5, wherein: The content ratio of the structural unit UA is 70% by mass or more based on all monomer units of the acrylic pressure-sensitive adhesive polymer.
7. The stripping method according to claim 1, wherein: The adhesive layer is formed of an adhesive composition containing an acrylic adhesive polymer, The adhesive composition includes 70% by mass or more of the acrylic adhesive polymer relative to the total amount of polymers included in the adhesive composition.
8. The stripping method according to claim 7, wherein: The adhesive composition further includes a vinyl polymer having a glass transition temperature of 30° C. or higher and 200° C. or lower and a number average molecular weight of 500 or higher and 10,000 or lower.
9. The stripping method according to claim 8, wherein: The content of the vinyl polymer is 0.5 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the acrylic pressure-sensitive adhesive polymer.
10. The stripping method according to claim 1, wherein: The storage modulus of the adhesive layer at a temperature 5° C. higher than the glass transition temperature Tg1 is 1 MPa or more and 1000 MPa or less.
11. The stripping method according to claim 1, wherein: The cooling temperature is below 0°C.
12. The stripping method according to claim 1, wherein: The adhesive layer has a peel strength of 3N / 25mm or more on an ABS plate at 85°C and a peeling speed of 300mm / min.
13. The stripping method according to claim 1, wherein: The adhesive material is in the form of a film or a plate.
14. The stripping method according to claim 1, wherein: The pasting material is a decorative film.
15. The stripping method according to claim 1, wherein: The pasting material is a glass plate.
Citation Information
Patent Citations
Tacky agent composition and tacky sheet using the same
JP1997291258A
Re-peelable self-adhesive sheet
JP2003160765A
Antiviral agent containing yttrium or yttrium compound, glaze containing antiviral agent, and antiviral sanitary ware coated with glaze
JP2022184066A